An update on the role of Hfq RNA Chaperone in resistance and virulence of Acinetobacter baumannii - SILVA, Lilian Caroliny Amorim; Leal, Nilma Cintra; Xavier, Danilo Elias (Revista Prevenção de Infecção e Saúde, 2022)
Introduction: The difficulty in treating Acinetobacter baumannii infections due to its high rate of resistance to antibiotics has led to the study of mechanisms inherent to the pathogen itself that can be used as effective targets in the treatment. Host Factor I Protein (Hfq) is an RNA chaperone generally necessary to assist in the connection between sRNAs and their mRNA target acting in the regulation of different genes, studies carried out in a range of bacterial species have shown that Hfq acts in a pleiotropic manner, contributing to virulence and response stress. Aim: To summarize current knowledge about the role of the Hfq RNA chaperone in the virulence and antibiotic resistance of Acinetobacter baumannii. Outlining: This is an integrative review developed from articles published in any language on Science Direct and PubMed platforms. Data collection and analysis were carried out between the period of April 2020 and February 2021. Results: Hfq shown to play important roles in cell growth, OMVs, metabolism of carbon sources, tolerance to physical and chemical stress, virulence through biofilm formation, fimbriae modulation, among others. Implications: Our work shows data that strengthen the role of Hfq in different aspects of virulence and environmental adaptation, including antimicrobial resistance of this pathogen, warning about the importance of Hfq as a possible future effective target in the treatment of these infections.